Quality in Customized Service in Hotel Management - Fonseca Saldaña, Ricardo Rolando (2017)
The research consists of: the customization of services, the influence of hotel management in profitability. Exploratory and descriptive research; sample of 24 hotel companies in the city of Lima, 384 customers were interviewed when paying. Instrument used: 21-item questionnaire. It was confirmed that the customization of services is related to hotel management based on three dimensions: Culture of Customized Service, Profitability and Competitiveness. For this contrast, the Chi-square hypothesis test was used. The research concludes that the customization of services ensures a better customer satisfaction and a high return to the hotel company. The human factor is crucial when implementing a customized service. The mechanisms contributing to customize hotel services are: searching of increasing sales and that customers’ order which is the main reason for customizing the services.